IMPLEMENTASI PEMIKIRAN JEAN JACQUE RUSSEAU DAN IMPLEMENTASINYA PADA KURIKULUM MERDEKA - Nasution, Salsabila; Karleni, Yeni; Marsidin, Sufyarma (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2024)
Education has a very important role in the development of a nation, especially in creating a generation that is ready to face future challenges. In Indonesia, the problem that is often faced in the world of education is the misalignment between the curriculum applied with the needs of society, as well as the rapid development of technology and global challenges. Therefore, we need a curriculum that is not only relevant to the times, but also able to facilitate the growth of individual learners. Jean Jacques Rousseau, an 18th-century philosopher, offered an insightful view of education that focused on the development of children's natural potential and their well-being. In his famous work Émile, ou De l'éducation (1762), Rousseau emphasized the importance of child-oriented education, which gives children the freedom to grow according to their natural stages of development. This thinking is very relevant to be used as a basis for the formulation of a better and holistic curriculum, which can support the education system in Indonesia in facing the challenges of the times.